KOMUNIKASI PEMBELAJARAN VIRTUAL DALAM SPIRIT MISERICORDIAE VULTUS - Norbertus Jegalus (Program Studi Filsafat Universitas Katolik Widya Mandira Kupang, 2021)
This article analyzes the problem of virtual learning communication that does not answer the demands of humanist education, namely carrying out not only